Porcine detection in commercial edible bird nest beverages using real time PCR targeting chromosomally encoded multiple porcine repetitive elements - Khairil Mokhtar, Nur Fadhilah; Aziz, Siti Nurain; Yusoff, Nurul Hanis; Raja Nhari, Raja Mohd Hafidz; Mohamad, Nurhidayatul Asma; Mohd Hashim, Amalia (Academic Press, 2024)
Popular consumption of edible bird nest beverage (EBNB) is driven by its claimed anti-aging properties. Incorporation of other anti-aging and protein-rich compounds such as collagen and gelatin increase the adulteration potential of EBNB especially those from economical feasible porcine sources. In this study, fifteen commercial EBNB products were examined for the presence of porcine DNA using real time PCR targeting multiple porcine repetitive element (MPRE42). DNA extracted using DNeasy Mericon Food Kit (Qiagen) obtained 0.08–17 ng/µl DNA that is ample for downstream qPCR. Universal qPCR assay successfully amplified conserved 18 S rRNA genes in all samples except for B7 which might dictate presence of PCR inhibitors such as phenolic compounds. Porcine-specific MPRE42 assay detected the presence of porcine DNA in 40% of the EBNB products (B5, B10, B11, B16, B17, B20) with Cq value ranging from 33.85±0.33–38.55±1.23. Analysis of EBNB product (B3) being spiked with different amounts of porcine gelatin shows that porcine-specific MPRE42 assay can detect up to 0.5% (w/w) porcine gelatin in B3. A linear correlation between Cq values of the DNA extracted from spiked samples and serial diluted porcine gelatin were obtained which demonstrates potential quantitative application of this assay. In overall, upon strict validation according to ISO/IEC 17025, the method described in this study has a huge potential to be applied by enforcement and authorities for porcine gelatin detection in EBNB products.